Health Literacy among Women Referring to Healthcare Centers of Zanjan City, Iran: A Cross-sectional Study - Mohtasham Ghaffari; Hossein Hatami; Sakineh Rakhshandrrou; Alireza Shoghli; Ahmad Heidari (Journal of Education and Community Health)
Background and Objective: Health literacy refers to a collection of skills, which enable the individuals to read, hear, analyze, and decide on the health-related issues. The possession of these skills by women have a significant effect on the improvement of health and happiness in their family and community. Regarding this, the aim of the present study was to determine health literacy level among the women referring to healthcare centers in Zanjan, Iran. Materials and Methods: This cross-sectional study was conducted on 323 women referring to the urban healthcare centers of Zanjan in 2016. The study population was selected using stratified random sampling technique. Data collection tools included a demographic questionnaire and Short Test of Functional Health Literacy in Adults. The data were analyzed in SPSS (version 21) using Pearson correlation test, t-test, and one-way ANOVA. Results: The mean health literacy among the participants was obtained as 71.56±17.8. According to the results, 22.6%, 22.3%, and 50.1% of the subjects had inadequate, borderline, and adequate health literacy, respectively. Furthermore, health literacy showed a significant relationship with education level (P<0.001) and occupational status (P=0.44). Conclusion: As the findings indicated, about half of the women had no favorable level of health literacy. Considering the critical role of women in preserving and promoting the health of their family and community, it is necessary to consider educational plan in order to improve the health literacy among this important group.